2022
DOI: 10.12982/cmujns.2022.005
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Microplastics by Microorganisms Isolated from Two Mature Landfill Leachates

Abstract: Microplastics are contaminants in the form of tiny plastic fragments diluted in terrestrial and aquatic environments. Recently, these contaminants have become a concern due to their negative impact on the quality of life of living things. The isolation and examination of microplastic degrading microorganisms' ability from two large mature landfills were conducted. Therefore, this study aims to obtain bacteria and fungi as bioremediation agents that can degrade microplastics. The isolation process was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…They can alter water properties, affecting algal growth, species composition, and nutrient dynamics in lakes. Microplastics also interact with fungi, with some capable of degrading them [98]. These impacts on microorganisms, bacteria, fungi, and algae can have cascading effects on lake ecosystems [99].…”
Section: Impacts On Microorganismsmentioning
confidence: 99%
“…They can alter water properties, affecting algal growth, species composition, and nutrient dynamics in lakes. Microplastics also interact with fungi, with some capable of degrading them [98]. These impacts on microorganisms, bacteria, fungi, and algae can have cascading effects on lake ecosystems [99].…”
Section: Impacts On Microorganismsmentioning
confidence: 99%
“…Similar studies reported Pseudomonas putida degrading HDPE by 12.07% (Hooda et al, 2023), Rhodococcus sp. degrading PP by 7.3% (Habib et al, 2020), Bacillus paramycoides degrading PS by 11.12% (Pikoli et al, 2022), Lysinibacillus sp degrading PE by 9% (Jeon et al, 2021), and Alcaligene faecalis degrading PA-6 by 27% (Oulidi et al, 2022). Hossain et al, (2023) reported that these plastics degrading bacteria have floc-forming ability.…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies reported Pseudomonas putida degrading HDPE by 12.07% (Hooda et al, 2023), Rhodococcus sp. degrading PP by 7.3% (Habib et al, 2020), Bacillus paramycoides degrading PS by 11.12% (Pikoli et al, 2022), Lysinibacillus sp degrading PE by 9% (Jeon et al, 2021), and Alcaligene faecalis degrading PA-6 by 27% (Oulidi et al, 2022). Hossain et al, (2023) reported that these plastics degrading bacteria have floc-forming ability.…”
Section: Introductionmentioning
confidence: 99%